Role of tour operators and travel agencies in promoting sustainable tourism - Andreea Marin-Pantelescu; Laurenţiu Tăchiciu; Sorinel Căpuşneanu; Dan Ioan Topor (Amfiteatru Economic Journal, 2019)
Due to its relative contribution and growing impact in the economy, tourism can play an important role in advancing the universal 2030 Agenda for Sustainable Development, including the application of bioeconomy principles, when governed with social responsibility, following sector specific standards as the ones provided by the Global Sustainable Tourism Council. In consideration of their privileged position within the tourism supply chain the study focusses on tour operators attempting to capture their current efforts toward social responsibility and the degree to which their activities comply with the applicable criteria for sustainable tourism. For three of the most important Romanian tour operators, the study provides an inventory of concrete ongoing activities and organizational governing principles in force which demonstrates a fairly high commitment toward social responsibility. However, companies recognise that such commitment it seeks to strengthen the corporate image rather than more fundamental sustainability goals. Among respondents, awareness of social responsibility principles and themes is higher than the awareness about specific sustainable tourism criteria. Moreover, the accent falls on the organization in question and only incidentally other supply chain links are involved. Further efforts have to be deployed in order to systematically implement the relevant sustainable tourism code, but companies manifest concern about the financial outcomes of such an investment.
Keywords: D83; M14; Q53; 330; Corporate Social Responsibility (CSR); sustainable management; tour operators and travel agencies; Global Sustainable Tourism Council (GSTC) Code